Physical Health Status and Frailty Index in Community Dwelling Older Adults in Tehran - Sima Ghasemi; Nastaran Keshavarz Mohammadi; Farahnaz Mohammadi Shahboulaghi; Ali Ramezankhani; Yadollah Mehrabi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Despite the increase in the elderly population all over the world, our knowledge is not sufficient for the status of their health in Iran. A comprehensive understanding of the health problems of this vulnerable group will help health planners to intervene effectively. This study was conducted to determine the physical health of elderly people in Tehran City, Iran. Methods & Materials In a cross-sectional study, 450 eligible elders were selected through a multistage stratified cluster random sampling method from district 5 in Tehran City, Iran. In order to collect the study information, a comprehensive "need assessment" questionnaire for elderly people in Iran was designed and validated. After approval of the Ethics Committee of the university and obtaining informed consent from the elderly, the questionnaires were completed by the researcher at home of the participants. The obtained data were analyzed by logistic regression test in SPSS version 16. Results About 90.9% of the studied elderly had at least one chronic illness with special treatment. The most prevalent reported disease was arthritis (62.4%) and the most commonly reported disorders and health problems were anxiety and fatigue, with a prevalence of 57.6% and 56.4%, respectively. Based on the multivariate logistic regression model, after controlling confounding variables, the frailty index had a statistically significant correlation with the physical health status  (OR=4.433, P<0.001). Conclusion Regarding the increasing prevalence of chronic diseases in older people, planning, and provision of services should be consistent with the current situation and changing needs of older people.